Benchmarking Numerical Freeze/Thaw Models. (August 2015) - Rühaak, Wolfram; Anbergen, Hauke; Grenier, Christophe; McKenzie, Jeffrey; Kurylyk, Barret L.; Molson, John; Roux, Nicolas; Sass, Ingo
Abstract: The modeling of freezing and thawing of water in porous media is an area of increasing interest. Examples include the modeling of permafrost degradation due to climate change, geotechnical applications in tunneling, and borehole heat exchanger performance in cold regions. Different code implementations have been developed and an interest has arisen in benchmarking different codes with analytical solutions, experiments, and numerical results. The name for this benchmark consortium is INTERFROST. Benchmark results are shown for a 1D analytical solution and two different 2D set-ups. All compared codes exhibit a similar behavior.